Ethnobotany of Anti-hypertensive Plants Used in Northern Pakistan - Malik, Khafsa; Ahmad, Mushtaq; Bussmann, Rainer W.; Tariq, Akash; Ullah, Riaz; Alqahtani, Ali S.; Shahat, Abdelaaty A.; Rashid, Neelam; Zafar, Muhammad; Sultana, Shazia; Shah, Syed N. (Frontiers in Pharmacology, 2018)
Hypertension is one of the most important factors responsible for cardiovascular ailments worldwide. It has been observed that herbal products and alternative herbal therapies played a significant role in decreasing hypertension. The aim of the current study is to provide significant ethnopharmacological information, both qualitative and quantitative on medicinal plants related to hypertension from Northern Pakistan. The documented data were quantitatively analyzed for the first time in this area. A total of 250 participants were interviewed through semi-structured discussions and questionnaires. Quantitative indices including FC (Frequency citation), FIV (Family importance value), RFC (Relative frequency of citation) and DCI (Disease Consensus index) were calculated. A total of 192 plant species, belonging to 77 families were reported to be used in treatment of hypertension in Northern Pakistan. The most dominant life form reported was herbs (54%), with decoction (72 reports) and leaves (55.1%) were commonly utilized plant part. Highest FIV was recorded in Lamiaceae (327 FIV). RFC ranged from 0.08 to 1.08% while DCI varied from 0.233 to 0.000. In this study original data was compared with thirty one previous national and international published papers from neighboring region to compare the medicinal uses and obtain some novel plant species. About 42% of the medicinal plant species were reported for the first time in treatment of hypertension in comparison to these 31 published papers. Different phytochemical activities of antihypertensive plants were also reported from literature. This research work documents the traditional knowledge of medicinal plants usage and provides baseline in designing clinical trials and pharmacological analysis for treatment of hypertension.